DEVELOPING SHARIA TOURISM IN FOSTERING REGIONAL ECONOMIC GROWTH (STUDY ON SHARIA TOURISM AT WEST NUSA TENGGARA) - Pelu, Ibnu Elmi A.S; Kurniawan, Rahmad; Akbar, Wahyu (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
The study investigated the development of sharia tourism to encourage the growth of potential tourist destination improve the regional economy as a sharia tourism destination, as well as legal policies in fostering sharia tourism in West Nusa Tenggara. The study employed qualitative research approach using concept of sharia tourism, the legal approach, and the sharia economic contextual approach. The findings revealed that: (1) from the road map view,Sharia tourism carried out by West Nusa Tenggara Provincial government was a continuation of sharia tourism by establishing 99 sharia tourism villages having local wisdom. In addition, developing sharia tourism was done by performing itself as a sharia tourist destination that did not ignore other tourism. It was also an avenur for a particular tourism choice in West Nusa Tenggara. The sharia tourism was considered successful in attracting foreign tourist destination, especially tourists from Muslim countries and some attractive Investment. The development of sharia tourism also tend to increase positively toward economic growth at West Nusa Tenggara. This can be seen from the data released by West Nusa Tenggara Tourism Department and Bank Indonesia, which showed economic growth of this region without mining sector in 2016 has reached 5.72% increase, in 2017 up to 7.10%, and in 2018, despite the earthquake, it continued to increase to 7.23% /year. (2) from the view of legal policies, West Nusa Tenggara already has strong legal legitimacy, so it can guarantee legal certainty in developing Sharia tourism destination. So hat, Sharia tourism destination in West Nusa Tenggara have clear policy directions in their ideas. It was strongly supported by policies, and implemented gradually.